Fermentasi Nira Nipah Skala 50 Liter Menjadi Bioetanol Menggunakan Saccharomyces Cerevisiae - Ade Sri Umaiyah; Chairul Chairul; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
One of the natural resources that can be utilized alternative into bioethanol is palm sap. Preparation stater done by culturing medium Saccharomyces cereviseae as developer on 10% yeast fermentation medium thus able to adapt and be ready to do the fermentation. This study aims to make bioethanol from palm sap 50-liter scale with variations in pH 4,5; 5 and 5,5 and fermentation time 24, 36, 48, 60 and 72 hours.. Batch fermentation process takes place with a stirring speed of 200 rpm and temperature of fermentation at room temperature (25-300C). The optimum fermentation conditions indicated on the initial conditions of pH 4,5 and fermentation time of 48 hours the acquisition of or 9% . Keywords: Bioethanol, palm sap, fermentation, Saccharomyces cerevisiae